Exploring power and influence in nutrition policy in Australia - Cullerton, K.; Donnet, T.; Lee, Andy; Gallegos, D. (Wiley-Blackwell Publishing Ltd., 2016)
© 2016 World Obesity Federation The food industry is often described as having more power and influence in nutrition policymaking than nutrition professionals, scientists and other practitioners working for the public interest; yet authors often allude to this point as an assumed truth, rather than an evidence-based fact. This paper applies social network analysis techniques to provide a concise evidence-based demonstration of the food industry's capacity to influence nutrition policymaking networks in Australia. Network analysis using four rounds of data collection was undertaken, and the capacity of individual actors and occupational categories to influence policy decision makers were analysed. Network graphs were developed using cluster analysis to identify the structure of clusters and the path distance of actors from decision makers. The assumed advantage for the ‘food industry’ was present both strategically in overall network position and with respect to the number of direct access points to ‘decision makers’, whereas ‘nutrition professionals’ were densely clustered together with limited links to key ‘decision makers’. The results demonstrate that the food industry holds the strategic high ground in advocating their interests to policymakers in the contexts studied. Nutrition professionals may be hampered by their reliance on strong ties with other nutrition professionals as well as limited direct links to ‘decision makers’.